Impact of Viral Radiographic Features on Antibiotic Treatment for Pediatric Pneumonia. Issue 5 (10th January 2022) - Geanacopoulos, Alexandra T; Lipsett, Susan C; Hirsch, Alexander W; Monuteaux, Michael C; Neuman, Mark I
Abstract: Background/Objectives: Chest radiograph (CXR) is routinely performed among children with suspected pneumonia, though it is not clear how specific radiographic findings impact antibiotic treatment for pneumonia. We evaluated the impact of viral radiographic features on antibiotic treatment among children undergoing pneumonia evaluation in the emergency department (ED). Methods: Children presenting to a pediatric ED who underwent a CXR for pneumonia evaluation were prospectively enrolled. Prior to CXR performance, physicians indicated their level of suspicion for pneumonia. The CXR report was reviewed to assess for the presence of viral features (peribronchial cuffing, perihilar markings, and interstitial infiltrate) as well as radiographic features suggestive of pneumonia (consolidation, infiltrate, and opacity). The relationship between viral radiographic features and antibiotic treatment was assessed based on the level of clinical suspicion for pneumonia prior to CXR. Results: Patients with normal CXRs (n = 400) and viral features alone (n = 370) were managed similarly, with 8.0% and 8.6% of patients receiving antibiotic treatment, respectively ( P = .75). Compared with children with radiographic pneumonia (n = 174), patients with concurrent viral features and radiographic pneumonia (n = 177) were treated with antibiotics less frequently (86.2% vs 54.3%, P < .001). Among children with isolated viral features on CXR, antibiotic treatment rates were correlated with pre-CXR level of suspicion for pneumonia. Conclusions: Among children with suspected pneumonia, the presence of viral features alone on CXR is not associated with increased rates of antibiotic use. Among children with radiographic pneumonia, the addition of viral features on CXR is associated with lower rates of antibiotic use, as compared to children with radiographic pneumonia alone. Abstract : The presence of viral radiographic features in isolation is not associated with increased rates of antibiotic use in children undergoing pneumonia evaluation in the emergency department. Chest radiograph may be useful in identifying children who can be safely managed off antibiotics.